Effects of caryophyllaeid cestode infestations of Clarias batrachus (Linn.) - Laboni, NN; Chandra, KJ; Chhanda, MS (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Effects of caryophyllaeid cestode infestations on Clarias batrachus was conducted during the period from August 2010 to July 2011. Fish samples collected from K.R. market, BAU campus came from various waterbodies. Sex, total length (cm), standard length (cm), head length (cm) and weight (g) were recorded. Five different species of caryophyllaeid namely Djombangia penetrans, Lytocestus indicus, L. birmanicus, L. parvulus and Bovienia serialis were identified from the host. Severe infestations of caryophyllaeid cestodes were found in C. batrachus. Changes in the nature of growth and loss of weight as a result of parasitic infestation were noticed. Accordingly length, weight and condition factors were found to be greatly affected. Loss of total length (8.73%) and the highest loss of mean head length (4.49%) were found in smaller infested length group fish. Loss of weight (1.63%) and the highest percentage loss of weight (26.38) were noticed in the small length group while it was 7.44 in large length group. The highest condition factor (1.13) was found in uninfested fish and lowest (0.85) in infested fish. Suggestions were made for further investigation on blood composition and gonadal development of infested host. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15594 J. Asiat. Soc. Bangladesh, Sci. 38(2): 135-144, December 2012